LICENSED PROFESSIONAL PERFORMANCE IN PHYSICAL EDUCATION AREA NON-SCHOOL: SHARES AND IMPLICATIONS. (Fiep Bulletin - online, 2013)
Schooling and professional experience of Physical Education is a much studied nowadays due to be field-dependent form of training, degree or bachelor's degree. Thus, this study sought to understand the relationship between training and performance of graduates in physical education graduates 2011pela Federal University of Piauí-UFPI working in non-school area, more specifically in bodybuilding. Sought to outline the profile of these subjects, and seek to know the reasons that influenced them to follow through this area. This qualitative study was descriptive and included a sample of 12 subjects, 06 men and 06 women. Data collection occurred from questionnaire and answered via email. The results show that these subjects were formed at a young age, with approximately 23 years, with an average time of completion of the course of four years, with the majority of natural Teresina-PI. The consensus is that the degree course in physical education UFPI not adequately prepare for the performance in the non-school, but identify themselves with this field of work; consider it profitable, but does not provide financial stability. In pursuit of this stability, crave jobs in school, especially in teaching at the college level. Experiments on stage not required (extracurricular) during the course exerted strong influence on current professional engagement. We conclude that even if identifying with area non-school graduates are in search of financial stability that think they can be reached on school grounds
Keywords: Physical Education; SchoolingandProfessional Performance; Extracurricular stage